2013
DOI: 10.12948/issn14531305/17.1.2013.02
|View full text |Cite
|
Sign up to set email alerts
|

A Lexical Analysis of Social Software Literature

Abstract: Social software are today more prevalent in organizational context, providing new ways for work and giving web users new opportunities for interaction and collaboration. This review aims to gain insight into the extent of available scholarly and professional literature on these new tools and into interests in this field. The analysis of the 5356 collected articles includes type of publication, year of publication, source, keywords in articles' titles and abstracts. The study here adopted a systematic approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In doing so, the question focussed on is which core questions for future research are identified in each paper. For this reason, the research work by Altamimi [3], Williams et al [16], and Berger et al [11] is outlined in the following.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…In doing so, the question focussed on is which core questions for future research are identified in each paper. For this reason, the research work by Altamimi [3], Williams et al [16], and Berger et al [11] is outlined in the following.…”
Section: Related Workmentioning
confidence: 99%
“…Altamimi [3] analysed the scientific literature on Social Software in a lexical study published in 2013. His objective was to systematically present the evolution of the literature since the development of social software and Web 2.0 technologies.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations